2018
DOI: 10.20396/zet.v26i2.8650093
|View full text |Cite
|
Sign up to set email alerts
|

Letramento em Matemática no PISA: o que sabem e podem fazer os estudantes?

Abstract: ResumoApresentamos resultados de pesquisa que buscou compreender desempenhos em Matemática de estudantes brasileiros, baseada em dados do PISA. Pesquisa foi conduzida envolvendo: análise exploratória dos microdados do PISA 2012, análise do conteúdo dos itens públicos de Matemática utilizados no PISA 2012 e aplicação desses itens a estudantes de 15 anos matriculados no 1º ano do ensino médio em duas escolas públicas. Foi evidenciada porcentagem significativa de estudantes brasileiros nos níveis mais baixos da e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 1 publication
0
5
0
4
Order By: Relevance
“…Even noting that the national results of Pisa 2012 showed that Brazilian students have achieved performance below the OECD average, we find that the average performance in Mathematics has shown a slight improvement (OECD, 2013;ORTIGÃO, 2018). Similarly, when obtaining results below the world average, with better performance in the Indeterminacy and Data subarea (26.5% below level 1), and with a scandalous difference of almost 20 points when compared to Changes and Relationships (46.3 % below level 1) (PEREIRA; MOREIRA, 2020), in which they achieved the worst performance, we reflect on the causes and consequences of this disastrous result, since the contents worked in the Change and Relations subarea appear more frequently in the seventh and eighth years of elementary school.…”
Section: Final Considerationsmentioning
confidence: 53%
See 1 more Smart Citation
“…Even noting that the national results of Pisa 2012 showed that Brazilian students have achieved performance below the OECD average, we find that the average performance in Mathematics has shown a slight improvement (OECD, 2013;ORTIGÃO, 2018). Similarly, when obtaining results below the world average, with better performance in the Indeterminacy and Data subarea (26.5% below level 1), and with a scandalous difference of almost 20 points when compared to Changes and Relationships (46.3 % below level 1) (PEREIRA; MOREIRA, 2020), in which they achieved the worst performance, we reflect on the causes and consequences of this disastrous result, since the contents worked in the Change and Relations subarea appear more frequently in the seventh and eighth years of elementary school.…”
Section: Final Considerationsmentioning
confidence: 53%
“…In this subscale, 40.3% of Brazilian students were not able to use the mathematical skills required by the simplest assessment tasks, which placed them below level 1 of the scale. A more indepth discussion of the Pisa results in this subarea can be found in Pereira and Moreira (2020), Ortigão et al (2018) and Lima (2016).…”
Section: Assessment In Mathematics In Pisamentioning
confidence: 92%
“…Mesmo observando que os resultados nacionais do Pisa 2012 mostraram que os estudantes brasileiros têm conquistado desempenho abaixo da média da OCDE, constatamos que o desempenho médio em Matemática tem apresentado tímida melhoria (OCDE, 2013;ORTIGÃO, 2018). Similarmente, ao se obterem resultados abaixo da média mundial, com melhor desempenho na subárea de Indeterminação e Dados (26,5% abaixo do nível 1), e com uma escandalosa diferença de quase 20 pontos quando comparados com Mudanças e Relações (46,3% abaixo do nível 1) (PEREIRA; MOREIRA, 2020), em que alcançaram o pior desempenho, refletimos sobre as causas e consequências desse desastroso resultado, uma vez que os conteúdos trabalhados na subárea Mudança e Relações aparece mais frequentemente no sétimo e no oitavo anos do Ensino Fundamental.…”
Section: Considerações Finaisunclassified
“…As deficiências na aquisição e consolidação da memória envolvendo o ensino e aprendizagem de matemática são confirmados por estudos realizados pela Ortigão et al (2018), os resultados obtidos demonstram que mesmo depois de muitos anos frequentando a escola, os alunos do ensino médio não alcançaram as competências matemáticas esperadas. Assim sendo, o professor de matemática precisa deixar um pouco o seu passado e suas crenças de que apenas testes, exercícios, e muita repetição colaboram para o processo de ensino-aprendizagem dos sujeitos, uma vez que esses métodos e aplicações apenas colaboram para a exclusão dos alunos e de sua aprendizagem.…”
Section: )unclassified